Spine Enlargement of Pyramidal Tract-Type Neurons in the Motor Cortex of a Rat Model of Levodopa-Induced Dyskinesia - Ueno, Tatsuya; Nishijima, Haruo; Ueno, Shinya; Tomiyama, Masahiko (Frontiers in Neuroscience, 2017)
Growing evidence suggests that abnormal synaptic plasticity of cortical neurons underlies levodopa-induced dyskinesia (LID) in Parkinson's disease (PD). Spine morphology reflects synaptic plasticity resulting from glutamatergic transmission. We previously reported that enlargement of the dendritic spines of intratelencephalic-type (IT) neurons in the primary motor cortex (M1) is linked to the development of LID. However, the relevance of another M1 neuron type, pyramidal-tract (PT) neurons, to LID remains unknown. We examined the morphological changes of the dendritic spines of M1 PT neurons in a rat model of LID. We quantified the density and size of these spines in 6-hydroxydopamine-lesioned rats (a model of PD), 6-hydroxydopamine-lesioned rats chronically treated with levodopa (a model of LID), and control rats chronically treated with levodopa. Dopaminergic denervation alone had no effect on spine density and head area. However, the LID model showed significant increases in the density and spine head area and the development of dyskinetic movements. In contrast, levodopa treatment of normal rats increased spine density alone. Although, chronic levodopa treatment increases PT neuron spine density, with or without dopaminergic denervation, enlargement of PT neuron spines appears to be a specific feature of LID. This finding suggests that PT neurons become hyperexcited in the LID model, in parallel with the enlargement of spines. Thus, spine enlargement, and the resultant hyperexcitability of PT pyramidal neurons, in the M1 cortex might contribute to abnormal cortical neuronal plasticity in LID.